2024
DOI: 10.1097/gox.0000000000005775
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Performance of the Combined Application of Two Robotic Systems in Microsurgery: A Two-center Study

Kai J. Wessel,
Viola A. Stögner,
Catherine T. Yu
et al.

Abstract: Background: Recent advancements in the development of robotic devices increasingly draw the attention toward the concept of robotic microsurgery, as several systems tailored to open microsurgery are being introduced. This study describes the combined application of a novel microsurgical robot, the Symani, with a novel robotic microscope, the RoboticScope, for the performance of microvascular anastomoses in a two-center preclinical trial. Methods: Six no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It offers wristed microsurgical and supermicrosurgical instruments, adding distal motion axes for an improved range of motion compared to conventional microsurgical instruments. Several preclinical studies revealed improved precision and ergonomics upon application of the Symani for the performance of microvascular anastomoses in vitro [ 1 3 ] and in vivo [ 4 ]. Furthermore, feasibility and safety of robot-assisted microsurgery was demonstrated in multiple initial clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…It offers wristed microsurgical and supermicrosurgical instruments, adding distal motion axes for an improved range of motion compared to conventional microsurgical instruments. Several preclinical studies revealed improved precision and ergonomics upon application of the Symani for the performance of microvascular anastomoses in vitro [ 1 3 ] and in vivo [ 4 ]. Furthermore, feasibility and safety of robot-assisted microsurgery was demonstrated in multiple initial clinical trials.…”
Section: Introductionmentioning
confidence: 99%